Electron Transfer Strategies to Regulate Carriers’ Separation for Intensive Pyroelectric Dynamic Therapy With Simultaneous Photothermal Therapy - Sun, Bingxia; Meng, Yun; Song, Tianlin; Shi, Jieyun; He, Xinhong; Zhao, Peiran (Frontiers in Chemistry, 2022)
Endogenic heat shock proteins and uneven local heat distribution are two main problems in traditional tumor hyperthermia therapy strategies. Aiming at solving these problems, we designed Au–SnSe–PVP nanomaterials (ASNPs) by modifying Au nanoparticles (Au-NPs) and biocompatible PVP on SnSe nanorods via a new reactive oxygen species production strategy. The ASNPs with excellent photothermal conversion performance can produce thermoelectric effects in response to temperature differences during photothermal conversion. The modification of Au-NPs can attract free electron (e–) to accumulate and promote the separation of e– and holes (h+) in the thermoelectric process, thereby further promoting e–-rich Au-NPs-induced H2O2 homolysis and h+–H2O half-reaction to generate hydroxyl radicals, realizing the synergistic application of photothermal therapy and pyroelectric dynamic therapy in tumor treatment.